Characteristics microplastics in gills and digestive tract of fish at seagrass ecosystem on Bintan Island, Indonesia - Idris Fadhliyah; Febrianto Try; Hikmat Nugraha Aditya; Pratomo Arief; Joei Koenawan Chandra; Yandri Falmi; Anggraini Rika; Wiwin; Ayu Puspa; Rahma Hidayati Jelita (BIO Web of Conferences)
Plastic waste is still present. Plastics are still required in food and drink containers because of their practical use and light, sturdy, and durable nature. Plastic waste can naturally decompose into small particles of less than 5 mm, called microplastics. Microplastics are currently of concern because of their impact on marine biota, including fish, in the seagrass ecosystem. This study aimed to determine the characteristics of microplastics found in fish organs, particularly in the digestive tract and gills, in the waters of Bintan Island and its surroundings. Sampling was performed on fish collected from fish trapped in gill nets. Ten fish samples were collected for each species, and the microplastics were analyzed using optical microscopy in the laboratory. The results showed that five forms of microplastics were found in the digestive tract and intestines of the fish, with abundances ranges between 49.67 – 122.38 particles/gram dry weight. The highest abundance of colors was found in both transparent colors in the digestive tract and black colors in the gills.